Pengujian Mesin Peniris Keripik Pisang untuk Industri Makanan Skala Kecil - Mhd. Iqbal; Tino Hermanto; Yopan Rahmad Aldori (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2025)
Manual oil draining on banana chips takes longer and leaves residual oil, affecting the texture and shelf life. This study uses centrifugal force to develop and test an oil-draining machine for banana chips. The method applied was experimental, with variables including rotation speed, draining time, and material capacity. The results show that the machine reduced oil content by 6% in 1 minute, improving crispness and shelf life.